The association between graduates' field of study and occupational attainment in West Germany, 1980–2008 - Markus Klein (Journal for Labour Market Research, 2016)
Over the course of higher education expansion and growing numbers of graduates, employers are supposed to have increasing difficulties to regard a higher education degree as reliable signal for productivity. As a consequence, they may take into account 'qualitative' differences such as graduates' field of study more often than in previous times when hiring labour market entrants. Both from a supply- and demand-side perspective graduates from humanities, social services or arts may be increasingly disadvantaged in terms of labour market outcomes compared to graduates from science, technology, engineering and mathematics over time. The article tests this argumentation by assessing changes in the relationship between graduates' field of study and risk of unemployment as well as access to the service class in West Germany between 1980 and 2008. Changes in returns to field of study may contribute to growing (social) inequalities among graduates amidst educational expansion and are therefore important to consider. Based on Microcensus data, the results show that field of study differences in terms of both labour market outcomes did not increasingly diverge over time. The paper concludes that due to a limited educational expansion and the prevalence of an occupationally segmented labour market higher education remains a good investment in terms of labour market returns in West Germany irrespective of graduates' field of study.
Keywords: 330; Studienfach - Auswirkungen; Berufserfolg; Hochschulabsolventen; Bildungsertrag; Studienfachwahl; Hochschulbildung; Bildungsexpansion; Westdeutschland; Bundesrepublik Deutschland